PENGELOLAAN LANSEKAP VISUAL YANG BERKELANJUTAN DI KAWASAN WISATA BOGOR, PUNCAK, CIANJUR JAWA BARAT - Nur Intan Mangunsong; Ina Krisantia; Rustam Hakim; Ida Bagus Rabindra (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2017)
Visual landscape is very important to promote a tourist destination. In Indonesia, the tourist area lost much of its visual appearance due to rapid development occurs. Therefore, the visual quality of the landscape need to be identified and quantified. The aim of this paper is to identify and to quantify the quality of the visual landscape in the tourist area of Bogor, Puncak Cianjur. This study uses a method Visual Resources Assessment Procedure (VRAP) (Richard C. Smardon, James F. Palmer, Alfred Knof and Kate Grinde, 1988), counting the total of visual elements such as water, vegetation, land surface, user activity as well as other considerations. The result of the calculation to get that Cisarua subdistrict has a high visual quality value, while the value of quality attraction Cibodas Botanical Garden has the highest value .Visual Landscape Management a). Visual Landscape management Zone a. Cipanas District entered in the class 1 category including preservation in the management class. b. Cisarua entered in the third class catergory including partial retention in the management class. b) Visual Resources Management Strategies a. Scenic management objective majority to protect the resourcesb. Scenic management strategy following the creteria